The major factors influencing the selection of building materials for sustainable buildings in Malaysia according to green building index (GBI) - Law, Geok Kian (2011)
Green building has gained momentum in Malaysia since the introduction of green building rating tool, Green Building Index (GBI) in 2009. The sustainable development is showing sign of picking up with increasing green buildings certified by GBI. Materials play an important role in green buildings as it can determine the performance of the building. Thus, the green building materials is important in the development process. In this dissertation, building material in green buildings is the focal of study. The major factors influencing the selection of building materials for sustainable buildings were investigated. 18 factors were extracted from the critical literature review to carry out survey questionnaire. A total of 37 survey questionnaires were collected from the designers. The survey using severity index indicated that availability of building materials (0.7569) and cost of building (0.7527) are the most critical factors. The results indicated that there is plenty of room to improve in the sustainable development in Malaysia. The availability of green building materials in Malaysia up to today’s date was investigated through desktop research. A comparison was made with the Singapore market. Singapore market was 7.8 times bigger than Malaysia market based on the comparison. Singapore has more green building materials because their Green Mark was launched earlier than GBI of Malaysia. The number of green materials increases as the sustainable development grows. The effectiveness of material assessments in GBI were established by carried out desktop research and which was compared with Green Mark of Singapore. The comparison shows that GBI have weaknesses in the material assessments and is not well structured compared to Green Mark. Green Mark has effective material assessments whilst some of the material assessments in GBI were not specific. GBI should incorporate more assessments related to building technologies rather than building products like Green Mark. Malaysian designers should not only concern with up-front cost but also to consider life cycle assessment of materials in cost where they can be incorporated in GBI for sustainable future.